Review article : Thelaziosis and Filariasis in Iraq (NTU Journal of Agriculture and Veterinary Science, 2024)
Thelaziosis and Filariasis are zoonotic diseases were caused by nematodes of genus Thelazia, and Felaria respectively which occur in many countries of the world , and transmitted to human by insects . The current review aimed to investigate the most important previous studies about Thelaziosis and Filariasis in Iraq. A total of 5 Thelazia and 24 for Filariasis abstractsandfull-textarticles ofreferencesforseveralwebsitescollectedaboutinfectionsrates.Tableswerecreatedthatincludedgeneralinformationofspeciestheparasitesunder the study in Iraq. It was concluded that there is a scarcity of research on these diseases , especially modern research. Only three species of the Thelazia were T.bosc, T. lacrymalis and T.gulosa and five species of filariasis were Dirofilaria immitis, D.repens, Setraria equine, Onchocerca gutturosa, O.linealis in addition to microfilaria in different location of the body